WHY CHILDREN DIFFER IN THEIR MATHEMATICAL ATTAINMENT AT PRIMARY SCHOOL? - Cowan, Richard (Anales de Psicología / Annals of Psychology, 2008)
Children differ considerably in their mathematical attainment in primary school. This paper reviews studies indicating the importance of socioeconomic status and heredity before considering basic calculation, the addition of single digit numbers and corresponding subtractions. Basic calculation proficiency varies with more general mathematical attainment. Delayed development of basic calculation proficiency is common in groups of children making slow progress in number whether or not they are also delayed in reading. Basic calculation might be important for mathematical development because it underpins arithmetic. Alternatively basic calculation might simply be a marker for mathematical development because the same factors affect its development as affect mathematical development. These factors include specific numerical ones such as counting and general cognitive factors such memory functioning, processing speed, language and intelligence. Finally practice is suggested to be as relevant to explaining differences in mathematical development as it is for other areas of expertise.